PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING - Gelu Savira Dwi Cahyani; Muhammad Riza Hafizi; Enriko Tedja Sukmana; Fuad Muhajirin Farid; Muhammad Noval (Universitas Lambung Mangkurat, 2024)
Good Corporate Governance is good and correct corporate governance to create added value for all stakeholders. A company's value is good if corporate governance is implemented well. Implementing good GCG will increase profits and reduce the risk of losses in the future so that it can increase company value. This research aims to examine the influence of Good Corporate Governance on Company Value with Profitability as a Moderating Variable in mining companies listed on the Indonesia Stock Exchange 2015-2019. The population of this research is all mining companies listed on the Indonesia Stock Exchange (BEI) in 2015-2019. The sampling method uses purposive sampling with a total sample of 3 companies. The data analysis method used is SEM-based Patrial Least Square (PLS) software. This research concludes that from the results of data analysis, based on predetermined decision-making, the results of this research are that Good Corporate Governance (GCG) has a positive and significant effect on company value. Then, profitability does not moderate the influence of GCG on company value.